2010
DOI: 10.1002/eji.201040474
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in tolerance induction for the treatment of autoimmune diseases

Abstract: Autoimmune diseases are characterized by the loss of tolerance toward self‐antigens and the induction of destructive immune responses leading to tissue damage. Most patients with autoimmune diseases are treated with immunosuppressive drugs that suppress the immune response in a non‐specific fashion, which is inevitably accompanied by several side effects. Antigen‐specific immunomodulation and patient‐tailored therapies are likely to solve these issues and to elicit long‐term protection against disease flares. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…DCs can be tolerogenic depending on their functional and maturation status and are able to delete or silence autoreactive T cells and facilitate the development of Tregs [66,67]. A pathway for DCs to traffic via the rostral migratory stream from the brain to the cervical LN, where they present antigen to T cells for inducing immune tolerance was observed in a mouse model of MS [68].…”
Section: Neural Antigens In Strokementioning
confidence: 99%
“…DCs can be tolerogenic depending on their functional and maturation status and are able to delete or silence autoreactive T cells and facilitate the development of Tregs [66,67]. A pathway for DCs to traffic via the rostral migratory stream from the brain to the cervical LN, where they present antigen to T cells for inducing immune tolerance was observed in a mouse model of MS [68].…”
Section: Neural Antigens In Strokementioning
confidence: 99%
“…The DC system is astonishingly complex and composed of different subsets with considerable plasticity [12]. It is important to note that tolerance induction is the major function of DC in the steady state as also outlined in the accompanying article by Maria Rescigno [13]. Only presentation of antigen by sufficiently matured DC expressing costimulatory molecules (such as membrane-bound CD86 and CD70 and/or soluble IL-12) will result in robust T-cell proliferation and differentiation, and thus effective T-cell immunity.…”
Section: Tumor Vaccines Must Exploit the Immunogenic Function Of DCmentioning
confidence: 96%
“…IL-4, IL-13) and result in autoimmune tolerance. (5) Tregs have been proved to attenuate RA via secretion of cytokines such as IL-25. TolDCs can express IDO and produce TGF-b and IL-10, which facilitate Foxp3?…”
Section: Reduction In Th17mentioning
confidence: 99%
“…Recent research has shown that a particular subset of DCs could modulate immune responses [4]. These DCs play a key role in maintaining both central and peripheral autoimmune tolerance, and the constitutive ablation of DCs destroys selftolerance, resulting in spontaneous fatal autoimmunity [5]. The DCs that induce autoimmune tolerance are called tolerogenic DCs (tolDCs).…”
Section: Introductionmentioning
confidence: 99%